ARGUMENTASI IBN ‘ATHA’ILLAH AL-ISKANDARIAH TENTANG TUHAN - Faza, Abrar M. Daud (UIN Sumatera Utara Medan, 2018)
Discourse on god is a study that never stops from time to time, especially in the study of Islamic thought. In the philosophical tradition, the philosophers describe three important approaches in the study and understanding of God: a) theological approach, b) cosmological approach and c) ontological approach. This paper aims to examine the existence of god. Proving God means making arguments to give certainty and truth about the existence of God. Theologians, philosophers, fuqahas, sufis, scientists and others never cease to express their thoughts about God. Thus various perceptions have been prepared according to rational, empirical (natural fact) evidence, as well as through religious experiences. Ibn 'Athaillah as Islamic thinker capable to elaborate sufistic, philosophical and fiqh approaches by not releasing the purity of theology, so as to present the uncorrect principle of tauhid.